DEVELOPMENT OF STUDENT ASSESSMENT INSTRUMENTS BASED ON COGNITIVE ASPECT SCIENCE APPROACH TO PHYSICS LEARNING IN DYNAMIC FLUID MATERIALS - Pane, Silfha Yanni; Sabani, Sabani (UNIVERSITAS NEGERI MEDAN, 2020)
This study aims to determine the validity of the instrument and determine the level of effectiveness of the development of assessment instruments for learning outcomes of cognitive aspects based on scientific approaches to dynamic fluid material based on the assessment of experts, teachers and class XI students of SMA Negeri 1 Stabat. The type of research used is research and development (R&D) using the 4-D model. The subjects in this study were 2 expert lecturers, 1 physics teacher, 9 small group test students and 33 large group test students. The object of this study is the validity and effectiveness of the instrument. The results of the experts' assessment showed the Aiken V index of 0.95 (good validity). The results of the validity of a small group test, 15 valid questions, and effective questions. While the results of the validity of a large group test, 12 valid questions, and effective questions. Then the development of student learning outcomes assessment instruments based on a scientific approach to class XI dynamic fluid material gets decent criteria and excellent assessments based on the criteria of experts, teachers and students.Keywords: assessment instruments, learning outcomes, scientific approaches, dynamic fluids